Revealing gaps in the project management literature: An application of multi-paradigm review to explanations of megaproject governance - Joe Sanderson (University of Birmingham, Birmingham Business School, 2013)
A multi-paradigm literature review methodology, 'interplay', is applied to alternative explanations of megaproject governance and performance. A two-fold categorisation of explanations, functionalist and interpretivist, is employed. The key insight is that despite important differences in epistemological orientation these two categories of explanation are essentially 'performative', which is expressed through a shared acceptance of the notion of actor farsightedness. This means that governance in megaprojects is primarily understood as static, convergent and patterned forms of organization (made order), while governance as discontinuous, divergent and fluctuating micro-processes of organizing is ignored. Having identified this explanatory gap, the article concludes with a call to refocus project governance research to include proper consideration of the multiple processes of organizing through which actors use, reproduce and transform governance as made order.
Keywords: 650; multi-paradigm review; paradigm interplay; functionalism; interpretivism; megaprojects; governance